PREVALENSI ENTEROBIASIS SERTA FAKTOR RESIKO YANGMEMPENGARUHI PADA ANAK-ANAK DI PANTI ASUHAN AL-WAHHAB SINAR MELATI 11 SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - , NISA ANESTESIA LIANA, dr. Tridjoko Hadianto, DTM&H, Mkes ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Helminthiasis is a disease caused by parasitic worms. Helminthiasis is common infectious agents of humans in developing countries and produce a global burden of disease that exceeds better-known conditions. The prevalence of enterobiasis is high all over the world. Infection occurs to all age groups with the highest prevalence amongst 5-14 years old and mostly occurs in places where children live, sleep, and play together. Orphanage becomes one of the places with high risk of E. vermicularis transmission. Objectives: To know the prevalence of enterobiasis in children who lives at Al Wahhab Sinar Melati 11 orphanage, Sleman, Daerah Istimewa Yogyakarta. Methods: This is an observational cross sectional study using descriptive analytic method. The subjects of this research are all 15 children between 5-14 years old living in Al Wahhab Sinar Melati 11 Orphanage , Sleman, Daerah Istimewa Yogyakarta. The samples taken by anal swab method. Results: According to the study done at the orphanage, 4 out of 15 chidren had positive results after being examined by anal swab method. The prevalence of enterobiasis in this study is quite high which is 26,67%. Conclusion: High incidence of enterobiasis may be due to several risk factors. The most contributing risk factors are the behavior amongst children living in orphanage that has lack of attention in maintaining individual and environmental hygiene. Dormitories or orphanage with high population increases the risk of enterobiasis due to the share use of several facilities and daily utilities. In conclusion, the knowledge and behavior of the children are the contrary where even though the knowledge about health and hygiene are high, the behavior doesnât follow.